Dinamika Kajian ‘Adālah al-Ṣaḥābah di Indonesia (2014–2023): Sebuah Tinjauan Sistematis - Kulsum, Umi; Ulfa, Aria (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2023)
The study of 'adālah al-ṣaḥābah or justice of the Prophet's companions is a central issue in the study of hadith, especially with regard to their credibility as narrators. This article systematically reviews the direction and development of 'adālah al-ṣaḥābah studies in Indonesia during the period 2014-2023 using the Systematic Literature Review (SLR) method. This research aims to track the direction of trends and developments in 'adālah al-ṣaḥābah studies in Indonesia in the 2014-2023 period and look at differences in methodological approaches and trends in 'adālah al-ṣaḥābah studies. The results of a literature search via Google Scholar show that the majority of research is descriptive and repeats the classic understanding pattern that all friends are fair without exception, as held by Ahlusunah Waljamaah. However, several contemporary studies have begun to question the validity of this view and propose criticism and deconstruction of the concept of collective justice. Figures such as Mahmud Abu Rayyah and Muhammad Thahir Albie proposed a re-evaluation of the definition of friends and the application of the principles of al-jarh wa al-ta'dīl at the level of friends. The main findings show a shift from a normative-theological approach to a historical critical approach. This study also highlights the limited biographical studies of individual friends and the lack of in-depth methodological exploration.